2006
DOI: 10.1162/rest.88.4.671
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Convergence across the United States: Evidence from County-Level Data

Abstract: We use U.S. county data (3,058 observations) and 41 conditioning variables to study growth and convergence. Using ordinary least squares (OLS) and three-stage least squares with instrumental variables (3SLS-IV), we report on the full sample and metro, nonmetro, and and regional samples: (1) OLS yields convergence rates around 2%; 3SLS yields 6%-8%; (2) convergence rates vary (for example, the Southern rate is 2.5 times the Northeastern rate); (3) federal, state, and local government negatively correlates with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(118 citation statements)
references
References 40 publications
(44 reference statements)
7
107
2
2
Order By: Relevance
“…This finding contrasts with evidence offered by, e.g., Higgins et al (2006), Glaeser et al (1995) and Connaughton and Madsen (2004) The findings reported above, therefore, call for detailed examination of conditions associated with Black populations in Mississippi. This is not an entirely negative conclusion.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…This finding contrasts with evidence offered by, e.g., Higgins et al (2006), Glaeser et al (1995) and Connaughton and Madsen (2004) The findings reported above, therefore, call for detailed examination of conditions associated with Black populations in Mississippi. This is not an entirely negative conclusion.…”
Section: Discussioncontrasting
confidence: 80%
“…In Higgins et al (2006) the full U.S. sample consists of 3,058 counties so we enjoyed the luxury of simply including all of our variables in the regression. In the present paper we consider each variable as a potential correlate with Mississippi county-level income growth.…”
mentioning
confidence: 99%
“…Table 6 and Figure 2 present tentative results for the estimation of (8) -apparent convergence. These are apparent, rather than convergence measures a la Mankiw, Romer, and Weil (1992) and the subsequent literature such as Islam (1995), Higgins, levy, and Young (2006), and Jones (1997Jones ( , 2002. But it is consistent with Bernard and Jones (1995) in establishing the link between From the tables as well as Figure 2, it is abundantly clear that Q and q are important to real per capita GDP, with the contribution of science publications being the strongest.…”
Section: Resultssupporting
confidence: 53%
“…Low-tech clusters that are heavily dependent on low taxes and cheap labour will have less competitiveness in their recruitment efforts than high-tech clusters (Galbraith, 1985). Higgins et al (2006) used county level data from 3058 US counties to study economic growth and measure the speed of convergence, concluding that convergence rates vary among the counties. Bostic et al (1997, p.41) argued that "capital (labour)-intensive cities should induce more labour (capital) inflow than less capital (labour)-intensive cities".…”
Section: Relations Among Regionally Heterogeneous Clusters In the Sammentioning
confidence: 99%